Bibliometric Studies In The Use Of Technology And Social Media For Marketing - Eka Yudhyani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
In order to gain a comprehensive view of marketing communications and understand the current research emphasis, this study evaluates the most relevant themes related to marketing communications through a bibliometric analysis using the keyword